Correlations of AKIP1, CXCL1 and CXCL2 expressions with clinicopathological features and survival profiles in cervical cancer patients - Wan, Xiaoyan; Hong, Zubei; Mao, Yuhong; Di, Wen (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: This study aimed to evaluate the correlation of A-kinase-interacting protein 1 (AKIP1) with C-X-C motif chemokine ligand (CXCL) 1 and CXCL2, and their associations with clinical characteristics and prognosis in cervical cancer patients. Methods: One hundred and fifty early-stage cervical cancer patients treated with surgical resection were reviewed and tumor tissue samples were obtained. Expression of AKIP1, CXCL1 and CXCL2 was detected by immunohistochemistry (IHC). Data of tumor features were retrieved, and disease-free survival (DFS) as well as overall survival (OS) were calculated. Results: AKIP1 expression was positively correlated with CXCL1 and CXCL2 expression in cervical cancer tissue (both P